SEASONAL RHYTHM AND DEVELOPMENT OF BETULA PENDULA L. IN BRICHMULLIN STATE FORESTRY - Ubaydullayev Farkhod Bakhtiyarullaevich; Xaitov Farkhod Djuraevich (Journals Park Publishing, 2024)
On May 11, 2017, the President of Uzbekistan Shavkat Mirziyoyev signed a decree “On the creation of the State Committee of the Republic of Uzbekistan for Forestry.” The State Forestry Committee is part of the Cabinet of Ministers complex for agriculture, processing of forestry products and consumer goods. The main objectives and areas of activity of the State Committee of the Republic of Uzbekistan for Forestry are mainly the implementation of a unified state policy in the field of forestry, aimed at the comprehensive expansion and rational use of forest resources.
Keywords: phenology, vegetation, flowering, fruiting, Brichmullinsky State Forestry, leaf fall, buds, factors, section Albae, B. pendula, air humidity, air temperature, self-seeding, seedlings, saplings, amplitude, etc.